Korps Mobile Brigade dalam mengatasi masalah DI/TII Jawa Barat 1950-1962 (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
The research examined Mobile Brigade Corps’ contribution in overcoming West Java’s DI/TII issue. Mobile Brigade Corps contributed to overcoming one of the domestic security interruption’s problems that happened in Indonesia in the 1950’s decade, namely West Java’s DI/TII. However, that contribution from Mobile Brigade Corps is unpopular. Then, the main question in this research is how is the contribution of the Mobile Brigade Corps in overcoming West Java’s DI/TII affairs. The method used in this research was a historical research method, with four research steps, namely heuristics, criticism, interpretation, and historiography. The research technique used for collecting data was literature and documentation study. Based on this research’s result, West Java was in an emergency state (SOB)/dangerous situation in the 1950’s decade. It was because, at that time, the security condition in West Java was worsened due to the domestic security interruption problem caused by West Java’s DI/TII. Mobile Brigade Corps involved in overcoming West Java’s DI/TII affairs because at that time, Djawatan Kepolisian Negara was involved in the task of overcoming that West Java’s DI/TII for seconded to Tentara Teritorium III/Siliwangi, Mobile Brigade Corps used because it is the paramilitary troops from Djawatan Kepolisian Negara. The efforts from Mobile Brigade Corps were formed by the Ranger Troops and mobilized Mobile Brigade Corps troops, including the Ranger Troops, in the domestic security operation to overcome West Java’s DI/TII affairs.
Keywords: DI/TII West Java; Indonesian National Police; Mobile Brigade Corps; Mobile Brigade